Impact of Erythrocyte Duffy Antigen Genetic Polymorphism on the Distribution of GroB-T, a Novel Human CXC Chemokine - Timothy W Hepburn; LeeAnn P Tobia; Wei Shi; Timothy A McIntyre; Charles B Davis (Frontiers Media S.A., 2007)
Purpose. GroB-T, a human CXC chemokine, has been studied for its potential to mobilize stem cells. Chemokines bind specifically to receptors on target immune cells but also to a homologous erythrocyte blood group antigen, the Duffy Antigen/Receptor for Chemokines (DARC) that is subject to genetic polymorphism in humans. A mutation in the DARC gene is common among African Americans and results in lack of expression of the erythrocyte antigen. We used a combination of in vitro studies of GroB-DARC interaction and pharmacokinetic simulation to anticipate the potential impact of this polymorphism on the pharmacokinetics of GroB-T. Methods. [125I]GroB-T was incubated in Caucasian blood to characterize the concentration dependence of the blood to plasma concentration ratio (B/P). Affinity and capacity of binding was estimated by Scatchard analysis; specificity was investigated by competitive displacement with a CC chemokine. The B/P value (7 nM) was then determined in blood from 8 African American subjects. Duffy antigen expression was determined by antibody agglutination. A pharmacokinetic model was developed which accounted for blood-cell binding. Simulations were performed to explore effects of dose regimen and DARC expression on the GroB-T plasma concentration-time profile. Results. GroB-T affinity and capacity for DARC (Caucasian blood) were 23.0 +/- 1.2 and 37.7 +/- 0.6 nM, respectively; excess CC chemokine fully displaced [125I]GroB-T. Chemokine binding was highly correlated with the presence or absence of the Duffy antigen (p